Ulcerated subcutaneous nodules: The first presenting sign of gastric adenocarcinoma - Tulika Rai; Sermili Rini Singnarpi; Vijay Kumar; Shailesh Singh (Wolters Kluwer Medknow Publications, 2021)
Cutaneous metastasis from internal malignancies is rare and represents about 2% of all skin tumors. Cutaneous metastasis occur in about 0.2%-0.4% of gastric carcinoma cases, most commonly affecting the abdomen with neck, head, eyebrow, axilla, chest, and fingertips being the other sites. Here, we present a case in which cutaneous metastases presenting as multiple crateriform nodules were the first presenting signs of gastric adenocarcinoma.